A high performance hybrid MPPT control scheme for a grid connected PV system based three level NPCMLI - Vijay Muni, T; S. Srikanth, K; Venkatesh, N; L. Sumedha, K (International Journal of Engineering and Technology, 2018)
This paper discusses about usage of novel control strategy to extract maximum power in case of solar energy conversion system for renewable energy system applications with the power electronic technology based novel 3 level neutral point clamped inverter. Photovoltaic is one of the important renewable energy sources. Compared to other renewal energy sources photovoltaic energy is clean and abundantly available. Solar power is considered a very promising source for electric power generation. It is generally seen that the renewable energy system is highly stochastic in nature and does not guarantee continuous power throughout the period. The solar based renewable energy resource has to be coupled with the existing conventional gird which might overcome the stochastic behavior of the non conventional resources. To meet the demand of the various types of customers, the proposed combination or generation mix is highly desirable and ray of hope for future generation. The efficient usage of solar based power generation is certainly possible when interfaced with the existing gird and meet the load requirement of diversified customers who are dependent on electric power.Low efficiency of the solar PV module leads to research and improvement about control technology of different sub-modules of solar based renewable energy generation system interfaced with the existing grid. Generally, the photovoltaic system rating is constrained by the efficiency of percentage output power obtained from the PV panel. In order to achieve this objective , controller to extract the maximum power from solar panel is designed and incorporated in the system known as Maximum power point tracking (MPPT). The return on investment is feasible with various constraints like environmental factors, other internal and external factors, only when the power output is optimum and maximum with the existing operating conditions.The maximum energy production that is power should be extracted from the solar panel in the given conditions. This process is called maximum powerpoint tracking. The point at each the proposed aim is reached, is called point of maximum power. The efficiency of the entire photovoltaic energy generation depends on the operating characteristic point. The load should ultimately get the optimum possible power obtained from the photovoltaic generation at the operating characteristic point [5]. Therefore, there should be some control logic or control technique in form of a suitable controller which is designated as maximum power point tracking (MPPT) controller. This controller is designed in such a way that the maximum power is obtained from the photovoltaic module.In this work, Direct Prediction Method and P&O is implemented as a hybrid MPPT control scheme grid connected PV system based NPCMLI. MLI helpful in increasing dynamic performance of the PV system with the existing operating conditions. This MLI offers less harmonic disturbances and goes near to maximum possible power factor operation i.e. 1. The results are verified in Matlab /Simulink environment.